Modern ecological approaches to fish waste processing in the Ukrainian fishery - Glushko, Yuliia; Nahorniuk, Tetiana; Savenko, Nelya; Garkava, Kateryna (Problems of Environmental Biotechnology, 2024)
The purpose of the study was to analyze the main modern ecological approaches to fish waste processing and the level of their implementation in the world and domestic aquaculture.